1998
DOI: 10.1179/joc.1998.10.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Increased Burn Patient Survival with Once-A-Day High Dose Teicoplanin and Netilmicin. An Italian Multicenter Study

Abstract: This is the final report of a large, controlled, multicenter Italian study on immuno- and chemotherapy in adult patients with burns affecting 20 to 95% of total body surface area (mean 35%). The antibiotic treatment of burn patients consisted of topical silver sulfadiazine, short-term antimicrobial chemoprophylaxis with pefloxacin (800 mg i.v. qd) for the first 4 days and polychemotherapy with teicoplanin (800 mg i.v. qd) together with netilmicin (300 mg i.m. qd) in one or more cycles of 5-12 days. At random, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As a result, 104 patients (16%) showed no infection, though the burns of these patients were relatively minor. However, the frequency of detected bacteria which is resistant to quinolones and aminoglycosides increased following treatment administration, and the usefulness of prophylactic administration of systemic antibiotics with this protocol could not be confirmed 95 Concerning studies on minor burns, Boss et al.…”
Section: Infection Controlmentioning
confidence: 98%
“…As a result, 104 patients (16%) showed no infection, though the burns of these patients were relatively minor. However, the frequency of detected bacteria which is resistant to quinolones and aminoglycosides increased following treatment administration, and the usefulness of prophylactic administration of systemic antibiotics with this protocol could not be confirmed 95 Concerning studies on minor burns, Boss et al.…”
Section: Infection Controlmentioning
confidence: 98%
“…Burn wound sepsis is the primary cause of death in early post burned period and is often characterized by massive invasive infection. 19 the ineffectiveness of systemic antibacterial therapy in combating such infection is due primarily to the avascular nature of the burn wound. In the absence of proper vascular channels and cellular host defense mechanism, 20 the systemically administered antibiotics cannot reach the site in effective concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter collaborative study carried out in Italy, 634 patients with extensive burns (mean age, ˜40 years; mean burned area, 35% TBSA) were treated by topical application of silver sulfadiazine and 4‐day administration of pefloxacin (a quinolone). As a result, 104 (16%) showed no infection, but the burns of all these patients were relatively minor, and bacteria resistant to quinolones and aminoglycosides increased after the administration, so the usefulness of preventive systemic administration of antibiotics by this protocol could not be confirmed Concerning studies on minor burns, Boss et al .…”
Section: Infection Control Cq15: Is Preventive Systemic Administratiomentioning
confidence: 99%
“…As a result, 104 (16%) showed no infection, but the burns of all these patients were relatively minor, and bacteria resistant to quinolones and aminoglycosides increased after the administration, so the usefulness of preventive systemic administration of antibiotics by this protocol could not be confirmed. 80 Concerning studies on minor burns, Boss et al retrospectively compared the wound infection rate between 133 who underwent systemic administration of antibiotics and 161 who did not of the 294 outpatients with burns and reported that there was no difference in the infection rate (3.8% vs 3.1%) and that, while antibiotics were administrated to a significantly higher percentage of patients in those with a burned area of 5% TBSA or more than in those with a burned area of less than 5% TBSA, the infection rate was not reduced in the first group. 81 Various reports and opinions have been presented concerning what kind of patients should receive preventive administration of antibiotics.…”
Section: Infection Control Cq15: Is Preventive Systemic Administratiomentioning
confidence: 99%